Pertumbuhan Bibit Buah Naga (Hylocereus costaricensis) dengan Perbedaan Panjang Stek dan Konsentrasi Zat Pengatur Tumbuh - Nurfadilah '; Armaini '; Husna yetti (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Dragon fruit (Hylocereus costaricensis) is one of fruit trees that grow well in Indonesia, so it has a great chance to be developed. These opportunities must be balanced with the supply of seed. Cuttings material and Growth Regulator Substance (GRS) concentration a factor that must be considered in the cultivation of seedlings because it will affect the growth of it in the field. The research was conducted at dragon fruit plantation Tameran village Bengkalis regency. The time used in this research lasted from August to December 2012. The design used was a Completely Randomized Design (CRD) 3 x 3 factorial with 3 replication. The first factor is the length cuttings, which is 20 cm, 25 cm and 30 cm. While the second factor is the GRS concentration, which is 6 g/10 ml, 9 g/10 ml and 12 g/10 ml. The parameters measured were the time appeared root, root length, number of roots, root volume, time appeared shoot, shoot length, number of shoots seedling fresh weight gain and dry weight of seedlings. Data were analyzed statistically using analysis of variance (ANOVA) and further tested by further testing (DNMRT) level of 5%. Results shows of the best dragon fruit seedlings growing on a combination between the 30 cm long cuttings with 9g/10 ml GRS concentration. Keywords: Dragon fruit, long cuttings, GRS concentration.